Innovative design development of the acupuncture department in hospitals in Ningbo - Chenyi, Li (2019)
As people's increasing requirement on rehabilitation and Chinese medicine, acupuncture has been extensively spread all over the world. Furthermore, due to the acupuncture cost low, and it has a curative effect, more people require acupuncture therapy. The effective acupuncture department design could improve both the doctor's and the patient's outcome. However, there are few pieces of research on the acupuncture department design. This research focuses on the doctor's work efficiency in the acupuncture department. Through the method of literature review, observation and simulation, recommend layouts are given aim at improving the doctor's efficiency. It is found problems of confusing circulation, infection issues and patient's privacy-invading through observation. In addition, the layout of the acupuncture department is simulated and analyzed based on the space syntax theory. Furthermore, this research proposed recommendations based on the concept of the universal room.